Evaluation of the levels of Road service of the current and future main roads of the Kirkuk city - Safar, Zine El Abidine Ali (Journal of Economic, Administrative and Legal Sciences, 2018)
The city of Kirkuk grew and developed greatly in recent years in terms of geographical area, which extended into large parts. The area of the current urban space reached to 185 km2, where it was not more than 95 km2 before 2000, and its population increased to about 980 thousand capita from 480 thousand capita. Whereas the ownership of cars increased by 12 persons per car after, in which they were less than 100 person/ car in the same year, on the other hand the growth in roads construction was not comparable to growth in population, with the area and ownership of cars, thus the problems govern for the city in the transportation services. The Delays and traffic accidents as well as environmental pollution in the city increased. Therefore, it is necessary to study and analyze the spatial relationship between the daily traffic volume on the main street network in the city and the centers of daily movement of the population to the level of efficiency and degree of road services according to the design capacity available to each street. The results of the study showed that most of the main streets of the city have deteriorated levels of service, which created different urban and environmental problems for the city. These problems are further exacerbated in the future with the urban expansion of the city, the increase of its population and the ownership of its cars. The study results recommends a certain treatment for the same roads and other uses of the surrounding land use and traffic attraction places, which contribute in reducing congestion to the increase in volume of daily traffic flow and ease of access and communication between the parts of the city.
Keywords: street design capacity; carrying capacity; daily traffic volume; vehicle classification; standard vehicle; road service grade